The Existence of the Aceh Traditional Assembly Institution in Preserving Aceh Culture in Lhokseumawe City - Virgo, Adrian; Rahmi Novalita, Rahmi Novalita; Khairani, Cut (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This type of research is qualitative research. The location of this research was carried out at the Aceh traditional assembly institution, Lohkseumawe City. The informants in this research were the chairman of the Aceh traditional assembly, and members of the Aceh traditional assembly. The technique for taking informants uses snowball sampling technique. Data analysis techniques use observation, interviews, documentation. Data analysis techniques use data reduction, data display, and drawing conclusions. The results of the research show that the Acehnese traditional assembly institution in Lohkseumawe City has made good efforts to preserve Acehnese culture. Activities carried out in preserving Acehnese culture are carried out through; a) Socialization, b) Guidance and development of traditional legal life and customs, c) Training.